Mechanisms involved in the regulation of mRNA for M(2) muscarinic acetylcholine receptors and endothelial and neuronal NO synthases in rat atria - Ganzinelli, S (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Agonists of the M(2) muscarinic acetylcholine receptor (mAChR) increase mRNA for this receptor and mRNA for endothelial and neuronal isoforms of NO synthase (eNOS or nNOS). Here we examine the different signalling pathways involved in such events in rat cardiac atria. EXPERIMENTAL APPROACH: In isolated atria, the effects of carbachol on mRNA for M(2) receptors, eNOS and nNOS were measured along with changes in phosphoinositide (PI) turnover, translocation of protein kinase C (PKC), NOS activity and atrial contractility. KEY RESULTS: Carbachol increased mRNA for M(2) receptors, activation of PI turnover, translocation of PKC and NOS activity and decreased atrial contractility. Inhibitors of phospholipase C (PLC), calcium/calmodulin (CaM), NOS and PKC prevented the carbachol-dependent increase in mRNA for M(2) receptors. These inhibitors also attenuated the carbachol induced increase in nNOS- and eNOS-mRNA levels. Inhibition of nNOS shifted the dose response curve of carbachol on contractility to the right, whereas inhibition of eNOS shifted it to the left. CONCLUSIONS AND IMPLICATIONS: From our results, activation of M(2) receptors induced nNOS and eNOS expression and activation of NOS up-regulated M(2) receptor gene expression. The signalling pathways involved included stimulation of PI turnover via PLC activation, CaM and PKC. nNOS and eNOS mediated opposing effects on the negative inotropic effect in atria, induced by stimulation of M(2) receptors. These results may contribute to a better understanding of the effects and side effects of cholinomimetic treatment in patients with cardiac neuromyopathy.